Operating systems : a systematic view - Davis, William S.; Davis, William S. (Redwood City, California : Benjamin Cummings, 1992)
Provides students with an introduction to the principles of operating systems while guiding them through the operating systems used. This book is designed to show why operating systems are needed and what they do. It takes students through the principles of OS and illustrates them with examples
(Each Chapter concludes with a Summary, Key Words, Review Questions, Exercises.)1. What Is an Operating System? Basic Operating System Functions.Layers of Abstraction.Open Source and Proprietary Operating Systems.A Look Ahead.I. BASIC SYSTEM RESOURCES. 2. Hardware. Memory.The Processor.Microcode.Input and Output Devices.Secondary Storage.Communication Hardware.Linking the Components.3. Software and Data. Hardware, Software, and Data.Software.Data.4. Linking the Hardware Components. Linking Hardware.Architectures.The Hardware/Software Interface.II. BASIC OPERATING SYSTEM CONCEPTS. 5. The User Interface, the File System, and the IOCS. An Operating System's Basic Functions.The User Interface.The File System.The Input/Output Control System.Resident and Transient Routines.The Boot.6. Resource Management. Memory Management.Virtual Memory.Multiprogramming.Time-sharing.The Virtual Machine Concept.Peripheral Device Management.III. COMMUNICATING WITH THE OPERATING SYSTEM. 7. MS-DOS Commands. MS-DOS.Getting Started.The File System.Pipes, Filters, and Redirection.Returning to Windows.8. The Microsoft Windows User Interface. Windows XP.Working with the Windows File System.Other Features.9. The UNIX/Linux User Interface. UNIX.The File System.Working with the File System.Pipes, Filters, and Redirection.Shell Scripts.The Command Line and GUI Layers.IV. OPERATING SYSTEM INTERNALS. 10. The Intel Architecture. Introduction.Intel Architecture Overview.Memory Addressing.Task Management.Memory Protection.Interrupt Handling.Improving the Performance of the Intel Architecture.Intel's 64-bit Itanium Architecture.11. MS-DOS Internals. MS-DOS.12. Windows XP Internals. Windows XP.Windows XP Architecture.Process Management.Memory Management.Disk Management.File Management.Input Output Manager.The Registry.Multimedia Support.The 64-Bit Version.13. UNIX and Linux Internals. The UNIX System.Images and Processes.Getting Started.Time-slicing and Interrupts.Memory Management.The File System.UNIX Internals.Linux.14. Macintosh OS X Internals. Introduction.OS X Architecture.Darwin.Processor Scheduling.Memory Management.File Systems.Device Drivers.QuickTime.15. MVS Internals. Traditional Mainframes.Traditional IBM Mainframe Operating Principles.Operating System Functions.The Dispatching Process.V. NETWORKS. 16. Data Communication and Networks. Layers.Data Communication.The Public Communication Infrastructure.Networks.17. The Internet and the World Wide Web. The Internet's Infrastructure.Internet Addressing.TCP/IP, the Internet's Protocols.The World Wide Web.An Expanded Layered View.18. Client/Server Information Systems. Web Information Systems.Services.Middleware.Security.19. Windows 2003 Server. Introduction.The Windows 2003 Network Architecture.File Services.Print Services.Web Services.Media Services.Clustering Services.Peer-to-Peer Networks.Managing Windows 2003 Server.Using Windows 2003 Server from a Client Computer.20. Linux Networking. Introduction.Network Services.Linux File Services.Windows Interconnectivity.Print Services.Apache Web Server.Clustering.21. Novell NetWare. NetWare.File Systems.Printing Services.Novell Directory Services.Network Management.Novell Netware 6.5.Using NetWare.Appendix A: Number Systems, Data Types, and Codes. Appendix B: Summary of MS-DOS Commands. Appendix C: Summary of UNIX Commands. Appendix D: IBM OS/JCL. Glossary. Index.
Includes index.
Keywords: OPERATING SYSTEMS (COMPUTERS)